2011
DOI: 10.1111/j.1744-7348.2011.00524.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecogeographic structure of phenotypic diversity in cultivated populations of quinoa from Northwest Argentina

Abstract: A set of 34 quinoa populations from the Northwest Argentina region was characterised using quantitative and qualitative phenotypic traits in an experiment conducted in the province of Jujuy, Argentina. A selection of quinoa descriptors from the Bioversity International (former IBPGR) list was applied, and data were analyzed using descriptive and multivariate techniques. Morphological and phenological traits variation was observed among accessions collected in contrasted ecogeographic zones of this Andean regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0
13

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 24 publications
5
25
0
13
Order By: Relevance
“…Even though the Transition zone is not a specific sub-region, it presents higher altitudes and drier conditions than the Eastern humid valleys, and populations from this zone showed a close relationship to each other. In a parallel characterization of phenotypic diversity of the same Argentinean germplasm (Curti et al, 2012), populations showed a similar structure to the results presented here. A decreasing Eastward gradient of genetic diversity and in the number of private alleles of each cluster was observed in our study ( Table 4).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Even though the Transition zone is not a specific sub-region, it presents higher altitudes and drier conditions than the Eastern humid valleys, and populations from this zone showed a close relationship to each other. In a parallel characterization of phenotypic diversity of the same Argentinean germplasm (Curti et al, 2012), populations showed a similar structure to the results presented here. A decreasing Eastward gradient of genetic diversity and in the number of private alleles of each cluster was observed in our study ( Table 4).…”
Section: Discussionsupporting
confidence: 81%
“…To the South, there is a second dry valley called Valles Calchaquíes, which is similar to the Quebrada de Humahuaca in terms of climate (Lorenzini et al 1999; weather section in DiPPEC, http://www.dippec.jujuy.gov.ar/clima.html). Native quinoa accessions are distributed in all these types of environment: to the west, in the arid elevations of the Puna; to the east, in the slopes of the Oriental chain, and between the two extremes in the Quebrada de Humahuaca and the Valles Calchaquíes (Curti et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Dekara sap ve tohum verimleri belirlendikten sonra basit bir eşitlik vasıtasıyla (sap + tohum verimi) genotiplerin dekara biyolojik verimleri, tohum verimi / (tohum verimi + sap verimi) x 100 formülü ile hasat indeksleri ve hasat edilen her bir genotipten 100'er adet tohum 4 tekerrürlü olarak sayılıp, tartılmış ve sonra ortalaması alınıp 10 ile çarpılarak 1000 tane ağırlıkları (g) hesaplanmıştır. Curti et al, (2012) yetiştirdikleri 34 kinoa populasyonuna ait ortalama sap kalınlıklarının 2.8 mm ile 9.2 mm arasında değiştiğini ifade etmişlerdir. Yine Spehar and De Barros Santos (2005) Brezilya ekolojik koşullarında 26 kinoa hattı ile yürüttükleri bir çalışmada incelemeye alınan hatların ortalama sap kalınlıklarının 4.7 mm ile 7.6 mm arasında değiştiğini belirtmişlerdir.…”
Section: Introductionunclassified
“…Dal sayılarında oluşan bu farklılık, kullanılan çeşitlerin farklı genetik yapıya sahip olmaları ve boylanmalardaki farklılıklardan kaynaklanmış olabilir. Konu ile ilgili olarak Curti et al, (2012), Arjantin ekolojik koşullarında yürüttükleri bir çalışmada 34 kinoa populasyonunu ele almışlar ve kantitatif gözlemler sonucunda kinoa populasyonlarına ait dal sayılarının bitki başına 0 adet ile 24 adet arasında değişkenlik gösterdiğini ve ortalama dal sayılarının 8.7 adet bitki -1 olduğunu belirtmişlerdir. Oysa mevcut araştırmamızda incelemeye alınan kinoa çeşitlerinden elde edilen ortalama dal sayıları 13.90 adet bitki -1 olarak belirlenmiştir.…”
Section: Introductionunclassified
“…Çeşitler arasında sap kalınlıklarının farklı olduğu pek çok araştırmacı tarafından da ortaya konmuştur. Curti et al (2012), yetiştirdikleri 34 kinoa populasyonuna ait ortalama sap kalınlıklarının 2.8 mm ile 9.2 mm arasında değiştiğini ifade etmişlerdir. Yine Spehar and De Barros Santos (2005) Brezilya ekolojik koşullarında 26 kinoa hattı ile yürüttükleri bir çalışmada incelemeye alınan hatların ortalama sap kalınlıklarının 4.7 mm ile 7.6 mm arasında değiştiğini belirtmişlerdir.…”
Section: Bulgular Ve Tartişmaunclassified